2002
DOI: 10.1029/2002jd002131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asian air pollution transport and photochemistry on carbon monoxide variability and ozone production in subtropical coastal south China

Abstract: [1] Surface ozone and carbon monoxide (CO) measured from a relatively remote coastal station in Hong Kong are analyzed to study the effects of pollutant transport and associated ozone production on CO and ozone variations in the subtropical south China region. CO and ozone concentrations show a common minimum in summer and in the maritime air masses from the South China Sea and Pacific Ocean. They have higher values in other seasons and in the continental air masses that have passed over mainland Asia and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
(62 reference statements)
3
17
0
Order By: Relevance
“…The O 3 concentrations remained high during March-May, resulting in a broad spring peak which was in contrast to a sharp fall peak. This is in accordance with a typical pattern that has been observed in other remote sites over northeast Asia during the past decades (Chan et al, 2002;Jaffe et al, 1996;Kanaya et al, 2015;Kondo et al, 2008;Oltmans and Levy II, 1994;Tanimoto et al, 2005Tanimoto et al, , 2009Watanabe et al, 2005; Weiss-Penzias et al, 2004). In particular, the second peak of O 3 was the most noticeable at IORS along with Gosan in October, which was also observed in previous studies (Kanaya et al, 2015;Tanimoto et al, 2005).…”
Section: Ozone Variationssupporting
confidence: 90%
“…The O 3 concentrations remained high during March-May, resulting in a broad spring peak which was in contrast to a sharp fall peak. This is in accordance with a typical pattern that has been observed in other remote sites over northeast Asia during the past decades (Chan et al, 2002;Jaffe et al, 1996;Kanaya et al, 2015;Kondo et al, 2008;Oltmans and Levy II, 1994;Tanimoto et al, 2005Tanimoto et al, , 2009Watanabe et al, 2005; Weiss-Penzias et al, 2004). In particular, the second peak of O 3 was the most noticeable at IORS along with Gosan in October, which was also observed in previous studies (Kanaya et al, 2015;Tanimoto et al, 2005).…”
Section: Ozone Variationssupporting
confidence: 90%
“…Changes in CO and volatile organic compounds (VOCs) may also contribute to this trend through NO-peroxy radical reactions. Strong positive correlations between O 3 and CO concentrations were previously found in late spring to early autumn in this region (Chan et al, 2002), and O 3 formation in the Hong Kong region is VOC-limited (Huang et al, 2005 …”
Section: Changes Of Surface Ozone Levels and Related Species During 1mentioning
confidence: 53%
“…Numerous studies demonstrated that in addition to long-range transport (Chan, 2002;Guo et al, 2009;Wang et al, 2009) and local photochemical production (Ding et al, 2013b), tropical cyclones and mesoscale circulations are conducive to the occurrence of high-O 3 events (Yin, 2004;Huang et al, 2005;Yang et al, 2012;Jiang et al, 2015;Wei et al, 2016). In a number of studies, the tropical cyclone has been considered as the most conducive driver to the occurrence of O 3 episodes in Hong Kong (Yin, 2004;Ling et al, 2013) because it generally causes peripheral subsidence, stagnation air and inversion layers, which favor the production and accumulation of O 3 .…”
Section: H Wang Et Al: Ozone Pollution Around a Coastal Region Of Smentioning
confidence: 99%